Electrocortical signatures of attentional bias toward subliminal and supraliminal socially negative words in social anxiety - Gan, Shuzhen; Cai, Yanglong; Li, Weijun (Frontiers in Psychiatry, 2025)
BackgroundPrevious research has demonstrated that abnormal attentional bias toward social threats at different processing stages is pivotal for the development and maintenance of social anxiety. However, the temporal property and the neural indicators of this bias are still open to clarification. The present study employed event-related potential (ERP) methodology to investigate the attentional bias toward social threats at the early preconscious and later controlled processing stages, along with associated electrocortical indicators.MethodsSocially or non-socially negative words paired with neutral ones were presented subliminally and supraliminally in two dot-probe tasks, respectively. Twenty-six participants with high level of social anxiety (high SA) and twenty-four participants with low level of social anxiety (low SA) completed the tasks.ResultsThe results revealed that, compared to the low SA group, the high SA group specifically showed a significant N2pc in response to subliminal socially negative words, and the amplitude tended to correlate with anxious severity. Additionally, the high SA group exhibited greater amplitudes of parietal P3 in response to incongruent probes than congruent ones following both subliminal and supraliminal socially negative words.ConclusionThese results indicate that abnormal attentional bias of social anxiety includes both early preconscious attentional orienting to social threats and subsequent difficulty disengaging from conscious and unconscious social threats, as indexed by N2pc and parietal P3 components, respectively. Our study may hold clinical significance by providing electrophysiological markers for assessing the cognitive symptoms of social anxiety.